A Y-Al-Si-O dense composite ceramic and preparation method thereof

Through the ball milling mixing of high-purity Y-Si-O powder and Al2O3 powder and the discharge plasma pressurized sintering process, the problems of high sintering temperature and complex process of alumina ceramics are solved, and high density and good oxidation resistance are achieved. Y-Al-Si-O dense composite ceramics are suitable for aerospace fields.

CN116425541BActive Publication Date: 2024-12-20NAT UNIV OF DEFENSE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310153213.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2024-12-20
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

The existing alumina ceramic materials have problems with high sintering temperature, complex process, and long-term consumption, and lack of reports on the use of Y-Si-O ceramic powder as an additive to improve ceramic performance.

Method used

After mixing high-purity Y-Si-O powder and Al2O3 powder in ball mill, the discharge plasma pressurized sintering process is used to shorten the sintering time and reduce the sintering temperature to form a dense Y-Al-Si-O dense complex phase with high density. ceramics.

Benefits of technology

It has achieved the formation of high density ceramic materials at lower sintering temperatures, simplified process flow, reduced energy consumption, significantly improved oxidation resistance and thermal shock resistance, and is suitable for high temperature resistance in aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116425541B_ABST
    Figure CN116425541B_ABST
Patent Text Reader

Abstract

The invention discloses a Y-Al-Si-O dense composite ceramic and a preparation method thereof. The preparation method comprises adding high-purity Y-Si-O powder and alumina powder to water for ball milling and mixing, drying, crushing, and sieving to obtain a pre-sintered powder, and performing discharge plasma sintering and annealing treatment on the pre-sintered powder under pressure and protective atmosphere, and naturally cooling to obtain a Y-Al-Si-O dense composite ceramic. The preparation method of the invention can significantly shorten the sintering time, reduce the sintering temperature, and has a short preparation cycle and low cost. The obtained Y-Al-Si-O dense composite ceramic has high density, high strength, good oxidation resistance and thermal shock resistance, and good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high temperature resistant and oxidation resistant ceramic material preparation, and in particular to a Y-Al-Si-O dense composite ceramic and a preparation method thereof. Background Art

[0002] Alumina ceramics have the advantages of high strength, high hardness, good conductivity, good wear resistance, and high temperature resistance. They are one of the most commonly used materials in industrial production and are widely used in aerospace, chemical industry and other fields. According to the different alumina content, alumina ceramics are divided into high-purity type and ordinary type. The high-purity alumina content is higher than 99.9%, but its purity requirement is higher, and the sintering temperature is as high as 1655-1955℃. Therefore, ordinary alumina ceramics are more commonly used in the market, such as common corundum crucibles, corundum furnace tubes, corundum bearings, water valve plates, resistor substrates, integrated circuit substrates, packaging shells, etc.

[0003] Ordinary alumina ceramics reduce their sintering temperature or improve their performance in a certain aspect by adding other ceramic powders. Common additives mainly include zirconium oxide, titanium oxide, silicon oxide, yttrium oxide powder, etc. Patent document CN111752357A discloses a method for preparing a dense alumina ceramic product, which uses titanium oxide as an additive to improve the thermal shock resistance of the product, but its sintering temperature is relatively high (1555℃~1655℃), and the sintering time (1~6h) is relatively long. Patent document CN111178511A discloses a method for preparing high-toughness alumina ceramics, which impregnates and sinters the carbon fiber after plasma treatment, and then mixes it with the alumina slurry after ball milling and various additives, and uses powder injection molding to obtain a preliminary blank, and finally debinding and sintering. Although this process can effectively improve its toughness, the process is complicated, time-consuming, and the process control is relatively cumbersome. Patent document CN111565685A discloses alumina ceramics and its preparation method and application. By adding various additives such as magnesium oxide, calcium oxide, silicon oxide, titanium dioxide, iron oxide, cobalt oxide, chromium oxide, etc., a brown-red semiconductor packaging material is obtained. This process has many additives, and the amount of various additives needs to be accurately controlled to obtain the corresponding ceramic products. There is no report on the use of Y-Si-O ceramic powder as an additive to prepare composite ceramics. Y-Si-O ceramics have excellent properties such as anti-oxidation, low thermal conductivity, low thermal expansion, high temperature resistance, and chemical corrosion resistance. Therefore, it can further improve the performance of alumina ceramics in all aspects and has good application prospects in the field of high temperature resistant ceramics. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a Y-Al-Si-O dense composite ceramic with high density, high strength, good oxidation resistance and thermal shock resistance, as well as a preparation method of the Y-Al-Si-O dense composite ceramic which can significantly shorten the sintering time and reduce the sintering temperature.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions.

[0006] A method for preparing a Y-Al-Si-O dense composite ceramic comprises the following steps:

[0007] S1. Mix high purity Y-Si-O powder and Al 2 O 3 The powder is added into water for ball milling and mixing, and then dried, crushed and sieved to obtain pre-sintered powder; wherein the purity of the high-purity Y-Si-O powder is ≥95%;

[0008] S2. The pre-sintered powder obtained in step S1 is subjected to spark plasma sintering under a protective atmosphere: first, the temperature is raised to a plasma sintering temperature of 1555°C to 1555°C at a heating rate of 55°C 55i5 to 355°C 55i5; when the temperature rises to 155°C before the plasma sintering temperature, the pressure is increased to 15MPa to 155MPa; the plasma sintering is kept warm for 15i5 to 155i5; then, the temperature is lowered to an annealing temperature of 555°C to 1255°C at a cooling rate of 55°C 55i5 to 355°C 55i5; when the temperature is lowered to the annealing temperature, the pressure is reduced to 5MPa; the annealing is kept warm for 15i5 to 155i5; finally, the temperature is naturally lowered to room temperature to obtain a Y-Al-Si-O dense composite ceramic.

[0009] The preparation method of the above-mentioned Y-Al-Si-O dense composite ceramics, preferably, in step S2, the heating rate is 155℃55i5~255℃55i5, the plasma sintering temperature is 1255℃~1155℃, the plasma sintering insulation is 35i5~65i5, the cooling rate is 85℃55i5~155℃55i5, the annealing temperature is 755℃~1555℃, the annealing insulation is 35i5~65i5, and the pressure applied during the plasma sintering process is 35MPa~65MPa.

[0010] In the above-mentioned method for preparing the Y-Al-Si-O dense composite ceramic, preferably, in step S1, the high-purity Y-Si-O powder is X2-Y 2 SiO 5 or γ-Y 2 Si 2 O 7 The high purity Y-Si-O powder and Al 2 O 3The mass ratio of the powder is 1-9:1-9.

[0011] The above-mentioned method for preparing the Y-Al-Si-O dense composite ceramics is more preferably, in step S1, the high-purity Y-Si-O powder and Al 2 O 3 The mass ratio of the powder is 3-7:3-7.

[0012] The above-mentioned method for preparing Y-Al-Si-O dense composite ceramics, preferably, in step S1, the ball milling time is 2h to 12h, the drying temperature is 85°C to 155°C, the drying time is 6h to 36h, the rotation speed used during the crushing is 20,000 rpm 55i5 to 30,000 rpm 55i5, and the sieving mesh size is 555 mesh to 5555 mesh.

[0013] In the above-mentioned method for preparing Y-Al-Si-O dense composite ceramics, it is more preferred that in step S1, the ball milling time is 1h to 8h, the drying temperature is 155°C to 125°C, the drying time is 12h to 21h, and the sieving mesh size is 1555 mesh to 3555 mesh.

[0014] In the above-mentioned method for preparing the Y-Al-Si-O dense multiphase ceramic, preferably, in step S2, the protective atmosphere is one or more of nitrogen, helium and argon, more preferably nitrogen.

[0015] As a general technical concept, the present invention also provides a Y-Al-Si-O dense composite ceramic prepared by the preparation method of the above-mentioned Y-Al-Si-O dense composite ceramic.

[0016] The above-mentioned Y-Al-Si-O dense multiphase ceramics, preferably, have a density greater than 97%.

[0017] Compared with the prior art, the advantages of the present invention are:

[0018] 1. The present invention constructs a new Y-Al-Si-O dense multiphase ceramic material system, which mechanically mixes high-purity Y-Si-O ceramic powder and alumina powder. Without adding other sintering aids, the two can react at a relatively low sintering temperature to form a liquid low-temperature eutectic, thereby obtaining a ceramic material with a higher density.

[0019] 2. The preparation method of the present invention adopts a spark plasma pressure sintering process, which greatly shortens the time, reduces the sintering temperature, simplifies the process flow, reduces the sintering energy consumption, and greatly reduces the manufacturing cost compared to the traditional sintering method.

[0020] 3. The Y-Al-Si-O dense composite ceramic material prepared by the present invention has high density, low open porosity, and low thermal expansion coefficient, which greatly improves its oxidation resistance and thermal shock resistance compared with alumina ceramics. In addition, a new phase of yttrium aluminum garnet will react between Y-Si-O ceramic powder and alumina powder, which has a high melting point and good oxidation resistance, further improving the oxidation resistance of the composite ceramic. The composite ceramic is expected to be used in the field of high temperature resistance and oxidation resistance in aerospace. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD spectrum of the Y-Al-Si-O dense composite ceramic prepared in Example 1 of the present invention.

[0022] Figure 2 This is a SEM photograph of the Y-Al-Si-O dense composite ceramic prepared in Example 1 of the present invention.

[0023] Figure 3 This is the EDS spectrum of the Y-Al-Si-O dense composite ceramic prepared in Example 1 of the present invention.

[0024] Figure 4 This is a thermogravimetric curve of the Y-Al-Si-O dense composite ceramic prepared in Example 1 of the present invention.

[0025] Figure 5 This is a thermal expansion curve of the Y-Al-Si-O dense composite ceramic prepared in Example 1 of the present invention.

[0026] Figure 6 X2-Y obtained in Comparative Example 1 2 SiO 5 SEM images of bulk materials. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The materials and instruments used in the following embodiments are all commercially available.

[0028] Example 1

[0029] A method for preparing a Y-Al-Si-O dense composite ceramic of the present invention comprises the following steps:

[0030] S1, 155g, purity> 98% high purity X2-Y 2 SiO 5 Powder and 155g Al 2 O 3The powder was added to 255 g of deionized water and ball-milled for 6 h. After drying in an oven at 155 ° C for 15 h, the dried mixed powder was crushed with a 20,000 rpm 55i5 mill and sieved with a 2555 mesh sieve to obtain a pre-sintered powder.

[0031] S2. The pre-sintered powder obtained in step S1 is subjected to spark plasma sintering in a nitrogen protective atmosphere at a heating rate of 155°C 55i5. When the temperature rises to 1255°C, the pressure (mechanical pressure) is increased to 15MPa, and the temperature is continued to be raised to the reaction temperature of 1355°C for 55i5, and then the temperature is reduced to 1555°C at a cooling rate of 155°C 55i5. At the same time, the pressure (mechanical pressure) is reduced to 5MPa, and the mixture is annealed for 25i5. Finally, the mixture is naturally cooled to room temperature to obtain a Y-Al-Si-O dense composite ceramic.

[0032] The density and porosity of the Y-Al-Si-O dense composite ceramics obtained above were tested by drainage method, and the volume density of the obtained sample was 1.55g5c5 3 , density is 97.12% (density is volume density 5 theoretical density, theoretical density is 1.17g5c5 3 ), the porosity is 2.88%, and the open porosity is 5.2%. XRD and SEM characterizations were performed simultaneously, and the phase composition and micromorphology were as follows: Figures 1 to 3 As shown, the main phase of the composite ceramic is Y 3 Al 5 O 12 and a small amount of Al 2 O 3 , where Y-Si-O and Al 2 O 3 The reaction produces yttrium aluminum garnet and SiO 2 , and the SiO generated by the reaction 2 It is an amorphous structure with a low content, so it cannot be detected in the XRD spectrum. However, the EDS results corresponding to the SEM characterization show that the bulk material contains Si element, and the atomic percentage of these four elements is Y∶Si∶Al∶O=9.22∶5.13∶25.11∶65.21. The fracture morphology shows that the obtained bulk material has a high density and basically no pores can be seen, indicating that X2-Y 2 SiO 5 and Al 2 O 3 The powder reacts at high temperature to form a liquid phase, and hot pressing can obtain a block material with high density. The formation of the liquid phase is conducive to reducing the sintering temperature. At the same time, the thermal properties of the composite ceramic material are characterized. The results are as follows Figure 1 and Figure 5 As shown, Figure 1This is the thermogravimetric curve of the bulk material from room temperature to 1555°C in air. It can be seen from the figure that with the increase of temperature, the mass of the bulk decreases by 1.69% within 355°C, mainly due to the volatilization of free water and bound water in the sample. After that, the mass of the sample remains unchanged as the temperature increases, and the oxidation resistance is good. Figure 5 is the thermal expansion curve of the sample. As can be seen from the figure, as the temperature rises, the linear expansion of the sample gradually increases, and the corresponding linear expansion coefficient (i.e. thermal expansion coefficient) also increases accordingly. However, from room temperature to 555℃, the linear expansion coefficient is less than 6.3×15 -6 ·K -1 Compared with alumina ceramics, the composite ceramics of the present invention have significantly lower thermal expansion coefficients and excellent thermal shock resistance. According to mechanical property tests, the flexural strength of the bulk material is 233.5 MPa, the flexural modulus is 66.9 GPa, and the mechanical properties are good.

[0033] Comparative Example 1

[0034] The difference between this comparative example and Example 1 is that Al 2 O 3 Powder, directly high purity X2-Y 2 SiO 5 The powder is subjected to the sintering process in step S2, and the obtained X2-Y 2 SiO 5 The bulk material was characterized, and the volume density was 1.55g5c5 3 , density is 91.21% (X2-Y 2 SiO 5 The theoretical density of the block is 1.11g5c5 3 ), the porosity is 8.79%, of which the open porosity is only 5.7%, the bending strength is 257.7MPa, and the bending modulus is 65.7GP. Compared with Example 1, the material density of Comparative Example 1 is lower, and the mechanical properties are relatively poor, and the corresponding fracture morphology is as follows Figure 6 As shown in the figure, there are many pores in the sample, and the structure is basically closed, which indicates that the mixed Al 2 O 3 Composite ceramics made from powders have higher density and relatively better performance.

[0035] Example 2

[0036] A method for preparing a Y-Al-Si-O dense composite ceramic of the present invention comprises the following steps:

[0037] S1, 155g, purity> 98% high purity X2-Y 2 SiO 5 Powder and 25g Al 2 O 3The powder was added to 155 g of deionized water and ball-milled for 6 h. After drying in an oven at 155 °C for 15 h, the dried mixed powder was crushed with a 20,000 rpm 55i5 mill and sieved with a 2555 mesh sieve to obtain a pre-sintered powder.

[0038] S2. The pre-sintered powder obtained in step S1 is subjected to spark plasma sintering in a nitrogen protective atmosphere at a heating rate of 155°C 55i5. When the temperature rises to 1355°C, the pressure is increased to 15MPa, and the temperature is continued to be raised to the reaction temperature of 1155°C for 55i5. The temperature is then reduced to 1555°C at a cooling rate of 155°C 55i5, and the pressure is reduced to 5 at the same time. The powder is annealed for 25i5 at the temperature, and then naturally cooled to room temperature to obtain a Y-Al-Si-O dense composite ceramic.

[0039] The obtained Y-Al-Si-O dense composite ceramics were characterized and the sample volume density was 1.21g5c5 3 , density is 97.22% (theoretical density of the block is 1.33g5c5 3 ), the phase composition is mainly X2-Y 2 SiO 5 and Y 3 Al 5 O 12 , the flexural strength is 215.6MPa and the flexural modulus is 71.3GPa.

[0040] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a Y-Al-Si-O dense composite ceramic, characterized in that: The following steps are involved: S1. Add high-purity Y-Si-O powder and Al2O3 powder into water, mix them by ball milling, and then dry, crush and sieve to obtain pre-sintered powder; wherein the purity of the high-purity Y-Si-O powder is ≥95%; the high-purity Y-Si-O powder is X2-Y2SiO5 or γ-Y2Si2O7, and the mass ratio of the high-purity Y-Si-O powder to the Al2O3 powder is 1-9:1-9; S2, the pre-sintered powder obtained in step S1 is subjected to spark plasma sintering under a protective atmosphere: first, the temperature is raised to a plasma sintering temperature of 1000°C to 1500°C at a heating rate of 50°C / min to 300°C / min, and when the temperature rises to 100°C before the plasma sintering temperature, the pressure is increased to 10MPa to 100MPa, and the plasma sintering is kept warm for 1min to 10min, and then the temperature is reduced to an annealing temperature of 500°C to 1200°C at a cooling rate of 50°C / min to 300°C / min, and when the temperature drops to the annealing temperature, the pressure is reduced to 0MPa, and the annealing is kept warm for 1min to 10min, and finally the temperature is naturally reduced to room temperature to obtain a Y-Al-Si-O dense composite ceramic, wherein the main phase of the Y-Al-Si-O dense composite ceramic is Y3Al5O 12 .

2. The method for preparing the Y-Al-Si-O dense composite ceramic according to claim 1, characterized in that: In step S2, the heating rate is 100°C / min to 200°C / min, the plasma sintering temperature is 1200°C to 1400°C, the plasma sintering is kept for 3min to 6min, the cooling rate is 80°C / min to 150°C / min, the annealing temperature is 700°C to 1000°C, the annealing is kept for 3min to 6min, and the pressure applied during the plasma sintering process is 30MPa to 60MPa.

3. The method for preparing the Y-Al-Si-O dense composite ceramic according to claim 1, characterized in that: In step S1, the mass ratio of the high-purity Y-Si-O powder to the Al2O3 powder is 3-7:3-7.

4. The method for preparing the Y-Al-Si-O dense composite ceramic according to any one of claims 1 to 3, characterized in that: In step S1, the ball milling time is 2h to 12h, the drying temperature is 80°C to 150°C, the drying time is 6h to 36h, the rotation speed used during the crushing is 20,000 rpm to 30,000 rpm, and the sieving mesh size is 500 mesh to 5000 mesh.

5. The method for preparing the Y-Al-Si-O dense composite ceramic according to claim 4, characterized in that: In step S1, the ball milling time is 4 hours to 8 hours, the drying temperature is 100° C. to 120° C., the drying time is 12 hours to 24 hours, and the sieving mesh size is 1500 mesh to 3000 mesh.

6. The method for preparing the Y-Al-Si-O dense composite ceramic according to any one of claims 1 to 3, characterized in that: In step S2, the protective atmosphere is one or more of nitrogen, helium and argon.

7. A Y-Al-Si-O dense composite ceramic obtained by the preparation method of a Y-Al-Si-O dense composite ceramic as claimed in any one of claims 1 to 6.

8. The Y-Al-Si-O dense multiphase ceramic according to claim 7, characterized in that: The density of the Y-Al-Si-O dense composite ceramic is greater than 97%.